2020
DOI: 10.1038/s41368-020-0078-6
|View full text |Cite
|
Sign up to set email alerts
|

Human β-defensin 3 gene modification promotes the osteogenic differentiation of human periodontal ligament cells and bone repair in periodontitis

Abstract: Efforts to control inflammation and achieve better tissue repair in the treatment of periodontitis have been ongoing for years. Human β-defensin 3, a broad-spectrum antimicrobial peptide has been proven to have a variety of biological functions in periodontitis; however, relatively few reports have addressed the effects of human periodontal ligament cells (hPDLCs) on osteogenic differentiation. In this study, we evaluated the osteogenic effects of hPDLCs with an adenoviral vector encoding human β-defensin 3 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…The three cell growth phases, lag, log (exponential), and plateau, were observed from the cell growth curve measured by CCK8. Our team has already proved that rPDLCs transfected with Ad-hBD3 could successfully express hBD3 ( Li et al, 2020 ). Fluorescence images showed rPDLCs transfected with Ad-hBD3 after cultured for 3 days ( Figure 4B ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The three cell growth phases, lag, log (exponential), and plateau, were observed from the cell growth curve measured by CCK8. Our team has already proved that rPDLCs transfected with Ad-hBD3 could successfully express hBD3 ( Li et al, 2020 ). Fluorescence images showed rPDLCs transfected with Ad-hBD3 after cultured for 3 days ( Figure 4B ).…”
Section: Resultsmentioning
confidence: 99%
“…In our former study, hPDLCs transfected by adenovirus containing the hBD3 gene were observed to express the hBD3 protein for at least 7 days. After transfection, Ad-hBD3-hPDLCs showed higher expression of osteogenic-related genes and proteins than normal hPDLCs in inflammatory microenvironments ( Li et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations